Population of the invasive harlequin ladybird Harmonia axyridis (Coleoptera: Coccinellidae) from Pelješac Peninsula, southern Croatia - Ceryngier, Piotr; Romanowski, Jerzy; Szymańska, Justyna; Galanciak, Maja; Bardzińska, Marta; Romanowski, Mateusz (Studia Ecologiae et Bioethicae, 2013)
Samples of the invasive alien ladybird, Harmonia axyridis, were collected between 27 July and 8 August 2013 at four localities on the Pelješac Peninsula in southern Croatia. Altogether, 209 individuals were collected, of which 114 (54.5%) were males and 95 (45.5%) females. Three color forms were present in the samples: the non-melanic form succinea and the melanic forms spectabilis and conspicua. The form succinea clearly predominated (90.5% of collected individuals) followed by spectabilis (8.1%) and conspicua (1.4%). The ectoparasitic fungus Hesperomyces virescens, not previously reported from Croatia, was found on the elytron of one H. axyridis individual. The localities in Pelješac Peninsula mentioned in this paper are the southernmost of all Croatian localities so far reported to be colonized by H. axyridis.